Performance of laminated compreg oil palm wood (Elaies guineensis Jacq.) associated with the diffusion and compression on polymer loading - Abd Ghani, Muhammad Aizat (2014)
Treatment of oil palm wood (Elaeis guineensis) with phenol formaldehyde (PF) resin and subsequently compressing at high hot pressure of oil palm wood is one of the potential ways to enhance its dimensional stability and strength properties. Factors such as molecular weight of PF resin, concentration of PF resin, penetration of PF resin as well as thickness of the material and compression ratio (ratio of the final thickness to the initial thickness of wood) need to be considered for efficient treatment. Study was undertaken to determine the effect of diffusion and compression on polymer loading and performance of laminated compreg oil palm wood (OPW) which had been treated with low and medium molecular weight phenol formaldehyde (LmwPF and MmwPF). OPW strips with 80-100% MC were soaked in LmwPF and MmwPF solutions separately for 24 h. Then, the treated strips were wrapped in plastics and left for diffusion for 2, 4, or 6 days, followed by pre-curing them in an oven at 650C for 6 hours. The pre-cured strips were assembled parallel to each other to form three-layer laminated compreg OPW, followed by compressing them under hot press at 150⁰C for 20 min to compression ratios of 55%, 70% and 80%. Laminated untreated OPW bonded with commercial PF resin served as a control. The polymer loading, dimensional stability, mechanical properties and formaldehyde emission of the compreg laminated wood for each treatment condition were determined. The results showed that, the polymer loading, as indicated by weight percent gain (WPG) of the laminated compreg OPW was significantly affected by the diffusion and compression processes. LmwPG-compreg OPW had higher WPG compared to MmwPG-compreg OPW. Compared to the laminated untreated OPW, the compreg products had superior properties where the LmwPF compreg OPW showed better performance than MmwPF compreg OPW. It was also found that density, anti-swelling efficiency (ASE), mechanical properties and formaldehyde emission of laminated compreg OPW were positively correlated with polymer loading, whilst water absorption and thickness swelling were negatively correlated with polymer loading for both laminated compreg OPW. Formaldehyde emission of the LmwPF laminated compreg OPW was relatively higher while formaldeyhde emission for MmwPF laminated compreg OPW was found within the threshold limit between 0.16 mg/l to 2.0 mg/l.